Modern Arabic literature - Starkey, Paul, 1947- (Edinburgh University Press, 2006)
Provides an introduction to modern Arabic literature of the nineteenth and twentieth centuries. Designed as an introductory textbook for English-speaking undergraduates, this title attempts to situate the development of modern Arabic literature in the context of the medieval Arabic literary tradition.
Keywords: Arabic literature -- 1801- -- History and criticism.; Littérature arabe -- 19e siècle -- Histoire et critique.; LITERARY CRITICISM -- African.; LITERARY COLLECTIONS / General; Arabic literature; Literatur; Arabisch; Arabisch.; Since 1801; Geschichte 1800-2000; Electronic book.; Criticism, interpretation, etc.